Engineering and Technology Universities in India:Present Status and Future Prospects - Sonde, B. S. (Journal of Engineering Education Transformations, 2010)
The Paper discusses the useful and important role of Engineering and Technology education in the Indian University system, the 21st century challenges being faced by the technical professionals in the country leading to demands for special attention to these and brings out the need for Universities exclusively devoted to. Engineering and Technology disciplines. The present status of Engineering and Technology Universities in the country is then covered, followed by the future prospects in this sector.